Characterization of Fibers from Pineapple's Crown, Rice Husks and Cotton Textile Residues - Karen de Souza do Prado; Márcia Aparecida da Silva Spinacé (Materials Research, 2015)
Fibers from pineapple's crown (PCF), rice husks (RH) and cotton textile residues (RTF) were characterized by SEM, X-ray diffraction, FTIR and thermogravimetric analysis. Moisture content, water absorption, density and the distribution of the diameter of the fibers were also evaluated. RTF showed cylindrical microstructure with smooth surface, PCF showed cellular structure and the microstructure of RH is globular, showing cell pattern of the outer surface epidermis which is well organized and has a corrugate structure. PCF and RH showed crystallographic planes of cellulose I and RTF showed a mixture of cellulose I and cellulose II. RTF showed the highest degree of crystallinity and the lower moisture content and water absorption. These results occur because the RTF has no hemicellulose, as verified by FTIR. Comparing the three fibers, the RTF presented the lowest density and diameter. Furthermore, the onset degradation temperature of RTF was 40 °C higher than the PCF and the RH.